Nanoparticles for targeted delivery of antioxidant enzymes to the brain after cerebral ischemia and reperfusion injury - Yun, Xiang (Nature Publishing Group, 2013)
Stroke is one of the major causes of death and disability in the United States. After cerebral ischemia and reperfusion injury, the generation of reactive oxygen species (ROS) and reactive nitrogen species may contribute to the disease process through alterations in the structure of DNA, RNA, proteins, and lipids. We generated various nanoparticles (liposomes, polybutylcyanoacrylate (PBCA), or poly(lactide-co-glycolide) (PLGA)) that contained active superoxide dismutase (SOD) enzyme (4,000 to 20,000 U/kg) in the mouse model of cerebral ischemia and reperfusion injury to determine the impact of these molecules. In addition, the nanoparticles were untagged or tagged with nonselective antibodies or antibodies directed against the N-methyl- -aspartate (NMDA) receptor 1. The nanoparticles containing SOD protected primary neurons in vitro from oxygen-glucose deprivation (OGD) and limited the extent of apoptosis. The nanoparticles showed protection against ischemia and reperfusion injury when applied after injury with a 50% to 60% reduction in infarct volume, reduced inflammatory markers, and improved behavior in vivo. The targeted nanoparticles not only showed enhanced protection but also showed localization to the CA regions of the hippocampus. Nanoparticles alone were not effective in reducing infarct volume. These studies show that targeted nanoparticles containing protective factors may be viable candidates for the treatment of stroke.